Decomposing Philippine Inflation into its supply and demand components (2001-2023) - J. C. Punongbayan (University of the Philippines, School of Economics (UPSE), 2024)
Was the episode of high inflation in the Philippines in 2022 driven primarily by supply or demand factors? How did the relative contributions of supply and demand evolve over time? This study adopts the methodology proposed by Shapiro (2022) and Shapiro (2023) to disaggregate Philippine inflation into supply and demand components from 2001 to 2024. I find that supply factors were the more significant reason for the pandemic-era spike in inflation, consistent with recent studies. More generally, I demonstrate that this methodology is useful for inflation monitoring in an emerging market context, and also to inform monetary policy.
Keywords: E31; E32; E52; 330; inflation; supply and demand; Philippines